Hand Hygiene: Hand Washing vs. Hand Sanitizer for Killing the Germs - Dian Fajarwati Susilaningrum; Tri Ujilestari; Ariani Putri; Sofiya Salsabila; Kholifah Nurul Hidayah (Indonesian Journal of Biology Education, 2021)
This study was conducted to compare handwashing using soap and hand sanitizer to kill germs on hands. Hand washing is one of the preventive measures to avoid various diseases that can be transmitted through hands. In addition, the COVID-19 pandemic which has attacked almost all over the world has forced various levels of society to pay more attention to hygiene, especially hand hygiene which can be a bridge for the spread of the virus. The research conducted in this article uses qualitative research methods based on reviews and analysis from several journals related to the comparison of the effectiveness of handwashing using soap and hand sanitizer. The results showed that there was a difference in the number of microorganisms in the hands before and after washing hands. Soap and hand sanitizer can eliminate microorganisms because both of these ingredients contain ingredients that can reduce the number of harmful bacteria in the hands such as alcohol and triclosan. From the analysis of several journals related to the effectiveness of handwashing using soap and hand sanitizer can be concluded that hand washing using soap and water is considered more effective to eliminate microorganisms on the hands than just the use of hand sanitizer.